Antimicrobial Susceptibility of Autochthonous Aquatic Vibrio cholerae in Haiti - Baron, Sandrine; Lesne, Jean; Jouy, Eric; Larvor, Emeline; Kempf, Isabelle; Boncy, Jacques; Rebaudet, Stanilas; Piarroux, Renaud (Frontiers in Microbiology, 2016)
We investigated the antimicrobial susceptibility of 50 environmental isolates of Vibrio cholerae non-O1/non-O139 collected in surface waters in Haiti in July 2012, during an active cholera outbreak. A panel of 16 antibiotics was tested on the isolates using the disk diffusion method and PCR detection of seven resistance-associated genes (strA/B, sul1/2, ermA/B and mefA). All isolates were susceptible to amoxicillin-clavulanic acid, cefotaxime, imipenem, ciprofloxacin, norfloxacin, amikacin and gentamicin. Nearly a quarter (22.0%) of the isolates were susceptible to all 16 antimicrobials tested and only 8.0% of the isolates (n=4) were multidrug-resistant. The highest proportions of resistant isolates were observed for sulfonamide (70.0%), amoxicillin (12.0%) and trimethoprim-sulfamethoxazole (10.0%). One strain was resistant to erythromycin and one to doxycycline, two antibiotics used to treat cholera in Haiti. Among the 50 isolates, 78% possessed at least two resistance-associated genes, and the genes sul1, ermA and strB were detected in all four multidrug-resistant isolates. Our results clearly indicate that the autochthonous population of V. cholerae non-O1/non-O139 found in surface waters in Haiti shows antimicrobial patterns different from that of the outbreak strain. The presence in the Haitian aquatic environment of V. cholerae non-O1/non-O139 with reduced susceptibility or resistance to antibiotics used in human medicine may constitute a mild public health threat.